Genetic profiles of aerobic resistance and somatotype in male athletes of high performance adult futsal team in Brazil - Dantas, P. M. S.; Brüch, V. L.; Fernandes, P. R.; Fernandes Filho, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The study in focus is centered in the identification of the genetic profiles, aerobic resistance and somatotical type, that characterize male athletes, of high performance, participants of the adult Futsal Team in Brazil. Methods To present research it has the descriptive stamp with profile typology. N=66 _ high performance athletes in adult Futsal team in Brazil. Dermathoglyphics (1); Multiage Fitness Test (2); and Somathotype (3). The descriptive statistics, structuring in medium values and theirs derived. The dispersion analyses, combined to the curtose test. Results To observe to the literature corresponds the pattern, for the sports of games and resistance of speed, as it describes. Discussion/Conclusion The possibility of aggregation of the Dermathoglyphics to be demonstrated, as one more protocol of evaluations, especially, for the Futsal. The one that, in last analysis, it would confirm the Dermathoglyphics, also inserted, in ergometric motriticity.